Improvement of Andean Blueberries Postharvest Preservation Using Carvacrol/Alginate-Edible Coatings - Carolina Medina-Jaramillo (Polymers, 2020)
Edible coatings are attractive strategies for blueberries postharvest preservation. In this work, carvacrol/alginate coatings were developed for application on Andean blueberries. Coating formulations were prepared based on blends of sodium alginate (2% w/v), carvacrol (0%, 0.03%, 0.06% or 0.09%), glycerol, and water and applied to the fruits by dip-coating. Then, the fruits were immersed in a calcium batch to induce a crosslink reaction. Changes in the physicochemical and microbiological characteristics of the blueberries were monitored during 21 days of storage at 4 °C. Coated blueberries were better preserved throughout the 21 days of storage because of their lower respiration rate and water loss, in comparison with the uncoated ones. Besides, the coatings enhanced the appearance and the gloss of the fruits. Control fruits showed a significant decrease in the firmness, while, in the coated fruits, this critical postharvest quality was preserved during the entire storage. Coating formulations with 0.09% of carvacrol was the most effective in preventing mesophilic aerobic bacteria and molds/yeasts growth on the fruits during the storage. Edible carvacrol/alginate coatings can be considered as a useful alternative to complement the benefits of refrigerated storage by delaying post-harvest spoilage of Andean blueberries.